(3OQGSGJ aj GdeMGSHI GdeGdjI GdeJNUUI (B/s - (3GdbHGfj, KfGA Ydjs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3jJVef gPG GdcJGH eGjdj eMGSHI GdaQhY hCLRGA GdeTQhY hGdJbGQjQ GdeGdjI GdDbJI , GdeHjYGJ HGdJbSjW ,HVGYI GdCeGfI , GdeMGSHI Yf GdYedjGJ GdJj JJe HYedI CLfHjIs
Keywords: (3GdJbGQjQ GdeGdjIs; (3GdeMGSHI GdeGdjIs; (3eMGSHI GdaQhYs